Quality Outcomes in the Surgical Intensive Care Unit after Electronic Health Record Implementation - Flatow, V. H.; Ibragimova, N.; Divino, C. M.; Eshak, D. S. A.; Twohig, B. C.; Bassily-Marcus, A. M.; Kohli-Seth, R. (Applied Clinical Informatics, 2015)
Background: The electronic health record (EHR) is increasingly viewed as a means to provide more coordinated, patient-centered care. Few studies consider the impact of EHRs on quality of care in the intensive care unit (ICU) setting.Objectives: To evaluate key quality measures of a surgical intensive care unit (SICU) following implementation of the Epic EHR system in a tertiary hospital.Methods: A retrospective chart review was undertaken to record quality indicators for all patients admitted to the SICU two years before and two years after EHR implementation. Data from the twelve-month period of transition to EHR was excluded. We collected length of stay, mortality, central line associated blood stream infection (CLABSI) rates, Clostridium difficile (C. diff.) colitis rates, readmission rates, and number of coded diagnoses. To control for variation in the patient population over time, the case mix indexes (CMIs) and APACHE II scores were also analyzed.Results: There was no significant difference in length of stay, C. diff. colitis, readmission rates, or case mix index before and after EHR. After EHR implementation, the rate of central line blood stream infection (CLABSI) per 1 000 catheter days was 85% lower (2.16 vs 0.39; RR, 0.18; 95% CI, 0.05 to 0.61, p < .005), and SICU mortality was 28% lower (12.2 vs 8.8; RR, 1.35; 95% CI, 1.06 to 1.71, p < .01). Moreover, after EHR there was a significant increase in the average number of coded diagnoses from 17.8 to 20.8 (p < .000).Conclusions: EHR implementation was statistically associated with reductions in CLABSI rates and SICU mortality. The EHR had an integral role in ongoing quality improvement endeavors which may explain the changes in CLABSI and mortality, and this invites further study of the impact of EHRs on quality of care in the ICU.
Keywords: Electronic health records; quality improvement; critical care; surgical intensive care